ON PRIME LABELING OF SOME SPECIAL GRAPHS (International Journal of Food and Nutritional Sciences, 2022)
Let G=(V,E) be a graph. A bijection f:V→{1,2,…,|V|} is called a prime labeling if for each edge e=uv in E, we have gcd{f(u),f(v)}=1. A graph that admits a prime labeling is called a prime graph. In this paper, we prove that the Jewel graph Jn , Jelly fish graph Jm,n, the graph Sm,n , the Headwood graph ,the Butterfly graph, the Dumbbell graph are prime cordial graphs. We also characterize the n-sided Prism graph that are prime cordial.